Optimalisasi Lahan Kelapa Sawit (Elaeis guineensis Jacq.) Fase Belum Menghasilkan (TBM) melalui Sistem Tumpangsari Jagung dan Kedelai di Desa Batu Belah - Feri Agriani; Afdhal Afdhal; Sri Oktika Syahputri; Boris Kaido; Rizky Qurnia Zary; Fajar Aga Wandana (Indonesian Journal of Emerging Trends in Community Empowerment, 2026)
Oil palm (Elaeis guineensis Jacq.) is Riau Province's leading plantation commodity, covering approximately 3.40 million hectares, of which smallholders manage 67.28%. During the roughly three-year immature (TBM) phase, oil palm land generates no harvest income while maintenance costs continue, reducing farmers' earnings. This community service program aimed to improve the knowledge and skills of oil palm farmers in Batu Belah Village, Kampar District, in optimizing TBM land through a maize-soybean intercropping system. Activities included a partner-needs survey, extension training with field demonstration, technical mentoring, and evaluation. Results show improved farmer understanding of intercropping techniques, planting distance, and nutrient management, along with a shift in perception that companion crops do not hinder oil palm growth when shading and spacing are properly managed. Agronomically, soybean contributes nitrogen fixation through Rhizobium symbiosis, while maize root systems help improve soil structure. Supporting studies from several regions report Land Equivalent Ratio (LER) values above 1.2-1.5 for maize-soybean or maize-groundnut intercropping under immature oil palm, indicating more efficient land use than monoculture. The program also opens an additional income stream for farmers during the oil palm waiting period, strengthens institutional synergy between Politeknik Kampar and village government, and offers a model that could be replicated in other TBM areas across Riau.